Buscando a independência e autonomia da criança através da estimulação constante : a experiência da família da criança com síndrome de Down - Nunes, Michelle Darezzo Rodrigues (2010)
The purposes of the study have been to identify which is(are) the meaning(s) of living with a child who has Down syndrome and its impact in the family functioning, and also to develop a theoretical model about these families experience. Symbolic Interactionism and a The Grounded Theory was used as a theoretical and methodological referential, respectively. Also, the semi-structured interview was authorized as an instrument of investigation, in which ten families were part of the study. The data analysis was performed concurrently to the collection, according to the steps alleged by the referential. It was possible to realize that the experience is composed of two phenomena: Living through cloudy times and Mobilizing to move forward . The first one is related to the hard times the family lives through and in which there are many doubts and uncertainties on handling with a Down syndrome child; the latter is related to all the attitudes and strategies to provide a better quality of life and development to the child. Through these phenomena, the Central Criterion and the Theoretical Model were identified: Searching for children s independence and autonomy through constant stimulation , which comes to reflect the family s experience with a Down syndrome child in the population that was studied. With the purpose of helping the child overcome their own barriers, the family needs to mobilize and struggle, to adapt to their routine, to learn about the Down syndrome, to search for the necessary treatments, to choose a school and face prejudice. These are huge responsibilities and concerns, which require help, either financial or emotional, to successfully fulfill all these deeds. This mobilization for the child s development imposes restrictions and abdications from the family group for their benefit. Besides, the family lives all their life with expectations about the child s future, always looking for some control over it. Despite the difficulties found during the path, the love and the happiness that the child brings to the family is a boundless motivation. It shows the family s endless search for the child s development through stimulations to guide to a less dependent future, motivated by love. The results lead to a reflection about the importance of family nursing, in which the nurse needs to be observant. Hard times faced by the family are highlighted and go way beyond the shock of discovery, which cause concern, anxiety, doubts and sadness. Thus, nurses must search for other contact settings with these families other than the hospital one, since their needs extrapolate the moment of diagnosis.